1997
DOI: 10.1128/aem.63.6.2200-2205.1997
|View full text |Cite
|
Sign up to set email alerts
|

Photoreactivation compensates for UV damage and restores infectivity to natural marine virus communities

Abstract: We investigated the potential for photoreactivation to restore infectivity to sunlight-damaged natural viral communities in offshore (chlorophyll a, <0.1 g liter ؊1), coastal (chlorophyll a, ca. 0.2 g liter ؊1), and estuarine (chlorophyll a, ca. 1 to 5 g liter ؊1) waters of the Gulf of Mexico. In 67% of samples, the lightdependent repair mechanisms of the bacterium Vibrio natriegens restored infectivity to natural viral communities which could not be repaired by light-independent mechanisms. Similarly, exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 36 publications
1
50
1
Order By: Relevance
“…Our results revealed that viral abundance was also correlated with nanophytoplankton abundance, as well as with the depth and concentration of dissolved oxygen, which supports the hypothesis that viral abundance could also be influenced by environmental parameters (Guixaboixareu et al, 1996;Wommack et al, 1996;Noble and Fuhrman, 1997;Weinbauer et al, 1997;Jacquet and Bratbak, 2003;Clasen et al, 2008). However, Corinaldesi and colleagues (2003) reported that within large spatial scales, viral abundance was only dependent on bacterial activity and host cell abundance in highly eutrophic systems.…”
Section: Large-scale Spatial Distribution Of Viral Abundancesupporting
confidence: 85%
“…Our results revealed that viral abundance was also correlated with nanophytoplankton abundance, as well as with the depth and concentration of dissolved oxygen, which supports the hypothesis that viral abundance could also be influenced by environmental parameters (Guixaboixareu et al, 1996;Wommack et al, 1996;Noble and Fuhrman, 1997;Weinbauer et al, 1997;Jacquet and Bratbak, 2003;Clasen et al, 2008). However, Corinaldesi and colleagues (2003) reported that within large spatial scales, viral abundance was only dependent on bacterial activity and host cell abundance in highly eutrophic systems.…”
Section: Large-scale Spatial Distribution Of Viral Abundancesupporting
confidence: 85%
“…Noble and Fuhrman [32] also observed that low levels of UVA contributed very little to the loss of infectivity of bacteriophages in contrast to UVB. This may be due to the relatively low UVA intensity applied in these experiments since it is known that UVA is involved in the recovery processes of some viruses [36,40]. A possible e¡ect may also have escaped our attention as we did not measure viral infectivity directly.…”
Section: Inter-speci¢c and Virus Variabilitymentioning
confidence: 98%
“…The combined activities of these repair systems should enhance survival and maintenance of viral activity, particularly in the relatively UV-rich surface waters. While some large dsDNA algal viruses may encode for their own DNA repair enzymes, most viruses rely on repair mechanisms of their hosts, which are achievable only after DNA has been inserted into the host cell (Furuta et al, 1997;Weinbauer et al, 1997;Shaffer et al, 1999;Orgata et al, 2011;Santini et al, 2013). In the summer, Garza & Suttle (1998) found twofold lower decay rates of natural cyanophage communities as compared to isolates, whereas in the winter, they were equal, suggesting (seasonal) selection for viruses that encoding host-mediated repair mechanisms.…”
Section: Uvmentioning
confidence: 99%